Fiscal Imbalance?: Assessing the Revenue-Sharing Mechanisms of Bayanihan Federalism - Mendoza, Ronald U (Archīum Ateneo, 2018)
The release of the final draft of the Consultative Committee (Con-Com) to Review the 1987 Constitution, officially designated as “Bayanihan Federalism”, has spurred vigorous debate, with much discussion focusing on the fiscal repercussions of moving towards a federal form of government. This paper contributes to this discussion through an analysis of the revenue-sharing mechanisms of the Bayanihan Federalism draft, and the likely political acceptability levels of adopting them among existing local governments. While much remains inconclusive given ambiguities hounding the said draft, our analysis highlights several issues and trade-offs embedded in the revenue-sharing and functional assignment proposals of Bayanihan Federalism — especially when compared with the potential impacts of the July 3, 2018 Supreme Court decision on the Mandanas et al. v. Ochoa et al. case on the determination of local governments’ internal revenue allotments. In particular, heightened federal-regional transfers are likely to strain the federal government’s ability to sustainably fund its considerable expenditure responsibilities, while securing fiscal gains for local governments that are comparable to those of the Mandanas ruling could bring about major viability challenges for proposed regional governments.